Criminal Sanctions Against Empty Bilyet Giro Issuers in Indonesia - M. Zahlan M. Zahlan; Faisal Santiago; Megawati Barthos (CV. Publikasi Indonesia, 2023)
Bilyet Giro is part of banking services in Indonesia carried out by conventional commercial banks. Conventional commercial banks are closely related to people's economic activities. The use of Bilyet Giro as a means of payment began to be felt by businesses, so the introduction and use of Bilyet Giro is a sign that the public knows the important role of Bilyet Giro as a means of giral payment. For issuers who issue empty bilyet giro will receive administrative sanctions in the form of inclusion of the customer's name into the Blank Giro Withdrawal Black List, and the customer is required to return the remaining unused bilyet giro blanks. The name of the customer listed in the blacklist expires, and then can be accepted again as a bank customer. However, if the issuer of an empty bilyet giro has an indication and it should be suspected that after the investigation process it turns out that there is an element of fraud, criminal sanctions can be imposed as stipulated in the Criminal Code. Guarantee of legal certainty in the application of the principle stated in Article 1 paragraph (1) of the Criminal Code, namely that a person can only be punished for his actions, if criminal sanctions for those actions have been regulated in advance in the Law. No matter how evil an act is, it will not be punishable if there is no law prohibiting it and mentions its sanctions. (Article 1 paragraph (1) of the Criminal Code).